2013
DOI: 10.3122/jabfm.2013.04.120307
|View full text |Cite
|
Sign up to set email alerts
|

Pass Rates on the American Board of Family Medicine Certification Exam by Residency Location and Size

Abstract: Background:The Accreditation Council for Graduate Medical Education (ACGME) sets residency performance standards for the American Board of Family Medicine Certification Examination. This study aims are to describe the compliance of residency programs with ACGME standards and to determine whether residency pass rates depend on program size and location.Methods: In this retrospective cohort study, residency performance from 2007 to 2011 was compared with the ACGME performance standards. Simple linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
1
14
1
Order By: Relevance
“…Unfortunately, neither factor is directly related to the characteristics of a residency program, because the former is an important predictor of individual performance whereas the latter is a regulatory factor. Some evidence suggests that location and program size are associated with the pass rate of the American Board of Family Medicine (ABFM) ( 15 ) and American Board of Pediatrics (ABP) certifying exams ( 16 ). Moreover, recent studies have shown that the pass rate of the ABFM certifying exam was also associated with accreditation cycle length, opportunities for international experiences, and training in alternative medicine ( 17 ).…”
mentioning
confidence: 99%
“…Unfortunately, neither factor is directly related to the characteristics of a residency program, because the former is an important predictor of individual performance whereas the latter is a regulatory factor. Some evidence suggests that location and program size are associated with the pass rate of the American Board of Family Medicine (ABFM) ( 15 ) and American Board of Pediatrics (ABP) certifying exams ( 16 ). Moreover, recent studies have shown that the pass rate of the ABFM certifying exam was also associated with accreditation cycle length, opportunities for international experiences, and training in alternative medicine ( 17 ).…”
mentioning
confidence: 99%
“…Moreover, IM programs in this region had the highest average pass rate of the American Board of Internal Medicine [10]. Besides IM, both pediatric and family medicine residencies also witnessed outstanding performance in program board exams in this region [7,8]. In general, training programs, including gastroenterology fellowship programs, located in the Pacific region are very competitive compared to those in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the study design and types of residency programs considered, program characteristics that affect the pass rate of a board exam include: program size [6–9], location [7–9], accreditation cycle length [9], opportunities for international experiences [9], training in alternative medicine [9], ratio of full-time equivalent paid faculty to fellowship positions (FTP) [1012], proportion of trainees based on type of medical school [10,11], formal mentoring program [10], on-site child care [10], and average hours per week of regularly scheduled lectures or conferences [11]. A thorough literature search shows no similar studies in medical subspecialties, which may be a consequence of pass rates for subspecialty levels being unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a fascinating study and a call for action, Falcone et al 17 report publically available data on the average examination scores on the American Board of Family Medicine certification examination. They found that many US family medicine residency programs have low average examination scores and high failure rates among their graduates that do not meet the Accreditation Council for Graduate Medical Education recommendations.…”
Section: New Clinical Information and Reviewsmentioning
confidence: 99%